Sodium-ion battery

CN122950573APending Publication Date: 2026-10-20TOYOTA JIDOSHA KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202512016905.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-11
Filing Date
2025-12-30
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

[0032]根据本发明,能够提供一种容量维持率得到改善的钠离子电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention provides a sodium-ion battery with improved capacity retention. The sodium-ion battery of this invention sequentially comprises a positive electrode active material layer, a separator layer, and a negative electrode active material layer, all of which are impregnated with a non-aqueous electrolyte. The positive electrode active material layer contains a positive electrode active material comprising a transition metal element. Furthermore, the non-aqueous electrolyte comprises an electrolyte salt, a gel-based solvent, and a dinitrile compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a sodium-ion battery. Background Technology

[0002] As disclosed in Patent Documents 1 to 4, various non-aqueous electrolytes for sodium-ion batteries are known.

[0003] For example, Non-Patent Document 1 discloses a non-aqueous electrolyte containing dimethoxyethane as a solvent.

[0004] Furthermore, Patent Documents 1 and 2 disclose a non-aqueous electrolyte containing a dinitrile compound.

[0005] Patent Document 1: Japanese Patent Application Publication No. 2010-165674

[0006] Patent Document 2: Japanese Patent Publication No. 2023-545564

[0007] Patent Document 3: Japanese Patent Application Publication No. 2016-085890

[0008] Patent Document 4: Japanese Patent Application Publication No. 2023-003666

[0009] Non-patent literature 1: Zhengnan Tian et al., Electrolyte Solvation Structure Design for Sodium Ion Batteries, 2022, Advanced Science, Volume 9, Issue 22 Summary of the Invention

[0010] The inventors have discovered that in sodium-ion batteries where transition metal elements are included as the positive electrode active material, the capacity retention is insufficient when dimethoxyethane is included as a solvent in the non-aqueous electrolyte.

[0011] The purpose of this invention is to provide a sodium-ion battery with improved capacity retention.

[0012] The inventors have discovered that the above-mentioned problems can be solved by the following method.

[0013] <Method 1>

[0014] A sodium-ion battery, comprising, in sequence, a positive electrode active material layer, a separator layer, and a negative electrode active material layer.

[0015] The positive electrode active material layer, the separator layer, and the negative electrode active material layer are impregnated with a non-aqueous electrolyte.

[0016] The positive electrode active material layer contains a positive electrode active material comprising transition metal elements.

[0017] The non-aqueous electrolyte contains electrolyte salts, Glyme-based solvents, and dinitrile compounds.

[0018] <Method 2>

[0019] According to the sodium-ion battery of method 1, the non-aqueous electrolyte further comprises a carbonate-based solvent.

[0020] <Method 3>

[0021] According to the sodium-ion battery described in method 1 or 2, wherein,

[0022] The positive electrode active material is a layered rock salt type oxide.

[0023] The gyme-based solvent is a single gyme, a single gyme derivative, or a combination thereof, and

[0024] The dinitrile compound is adiponitrile, succinate, or a combination thereof.

[0025] <Method 4>

[0026] According to any one of methods 1 to 3, in the sodium-ion battery, the concentration of the dinitrile compound in the non-aqueous electrolyte, expressed in mM, is relative to the concentration expressed in m... 2 The ratio of the specific surface area of ​​the positive electrode active material, expressed as / g, is 200 to 1500.

[0027] <Method 5>

[0028] According to any one of the methods 1 to 4, in the sodium-ion battery, the concentration of the dinitrile compound in the non-aqueous electrolyte is in a ratio of 0.05 to 0.60 to the concentration of the electrolyte salt.

[0029] <Method 6>

[0030] In the sodium-ion battery according to any one of methods 1 to 5, the concentration of the dinitrile compound in the non-aqueous electrolyte is 50 mM to 600 mM.

[0031] Invention Effects

[0032] According to the present invention, a sodium-ion battery with improved capacity retention can be provided. Attached Figure Description

[0033] Figure 1 This indicates that Glyme-based solvents are coordinated to transition metal ions (M). + A schematic diagram of the state on ).

[0034] Figure 2 This is a schematic cross-sectional view showing an example of the sodium-ion battery of the present invention. Detailed Implementation

[0035] The embodiments of the present invention will now be described in detail. However, the present invention is not limited to the following embodiments, and various modifications can be made within the scope of the spirit of the invention.

[0036] <<Sodium-ion batteries>>

[0037] The sodium-ion battery of the present invention comprises, in sequence, a positive electrode active material layer, a separator layer, and a negative electrode active material layer, wherein the positive electrode active material layer, the separator layer, and the negative electrode active material layer are impregnated with a non-aqueous electrolyte. The positive electrode active material layer contains a positive electrode active material comprising a transition metal element. Furthermore, the non-aqueous electrolyte comprises an electrolyte salt, a gel-based solvent, and a dinitrile compound.

[0038] The inventors believe that, in sodium-ion batteries where transition metal elements are included as the positive electrode active material, one of the reasons for insufficient capacity retention when using a non-aqueous electrolyte containing dimethoxyethane as disclosed in Patent Document 1 is the dissolution of transition metal ions from the positive electrode active material.

[0039] Specifically, this is not bound by any theory, but is based on the following conjecture: that is, through repeated charge-discharge cycles, transition metal ions may sometimes dissolve into the non-aqueous electrolyte. Furthermore, as... Figure 1 The example illustrates that Glyme-based solvents such as dimethoxyethane are considered to be coordinated with dissolved transition metal ions (M... + This process stabilizes the transition metal ions, thus promoting their dissolution. It is believed that these dissolved transition metal ions are reduced and precipitated on the surface of the negative electrode active material layer. It is further believed that the reaction of this precipitated transition metal with sodium ions reduces the amount of sodium ions acting as carrier ions, leading to a decrease in battery capacity with charge-discharge cycles.

[0040] In contrast, the inventors unexpectedly discovered that in sodium-ion batteries where transition metal elements are included as positive electrode active materials, capacity retention can be improved by using a non-aqueous electrolyte containing dinitrile compounds in addition to a Glyme-based solvent.

[0041] As a reason, although not bound by any theory, the following conjecture is made: that is, it is believed that dinitrile compounds hinder... Figure 1 The example illustrates the coordination of transition metal ions with a gelleme-based solvent. Therefore, it is believed that the dissolution of transition metal ions into the non-aqueous electrolyte can be suppressed, thereby improving the battery's capacity retention.

[0042] The components that constitute the sodium-ion battery of the present invention will be described below.

[0043] The sodium-ion battery of the present invention sequentially comprises a positive electrode active material layer, a separator layer, and a negative electrode active material layer. For example... Figure 2 As illustrated, the sodium-ion battery 1 of the present invention may sequentially include a positive electrode current collector layer 10, a positive electrode active material layer 20, a separator layer 30, a negative electrode active material layer 40, and a negative electrode current collector layer 50.

[0044] The sodium-ion battery of the present invention can be a liquid battery.

[0045] The sodium-ion battery of the present invention can be a rechargeable battery.

[0046] Sodium-ion batteries can be in shapes such as button-shaped, laminated (pouch-shaped), cylindrical, or square.

[0047] Sodium-ion batteries can be manufactured by forming the aforementioned layers using dry or wet molding methods.

[0048] The sodium-ion battery of the present invention can be preferably used in at least one of hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), and battery electric vehicles (BEV).

[0049] The components that constitute the sodium-ion battery of the present invention will be described below.

[0050] <Positive current collector layer>

[0051] Examples of materials used as positive electrode current collector layers include SUS, aluminum, nickel, iron, titanium, and carbon.

[0052] <Positive Electrode Active Material Layer>

[0053] (Positive electrode active material)

[0054] The positive electrode active material layer contains a positive electrode active material comprising a transition metal element. In the sodium-ion battery of the present invention, the dissolution of transition metal ions from the positive electrode active material is suppressed by the dinitrile compound described later.

[0055] As a positive electrode active material, there are no particular limitations as long as it contains a transition metal element. Examples of such positive electrode active materials include Na-containing oxides such as layered active materials, spinel-type active materials, and olivine-type active materials. The positive electrode active material can be a layered rock salt type oxide, especially an O3-type layered rock salt type oxide. As an O3-type layered rock salt type oxide, it can be Na… xMO₂ (0<x≤1, M is at least one selected from Fe, Ni, Co, Mn, V and Cr), specifically, examples include NaFeO₂, NaNiO₂, NaCoO₂, NaMnO₂, NaVO₂, Na(Ni X Mn 1-X )O₂ (0<X<1) and Na(Fe X Mn 1-X )O₂ (0<X<1). In layered rock-salt type oxides, transition metal ions are prone to leaching from the positive electrode active material, so using such a positive electrode active material as a constituent material of the sodium-ion battery of the present invention is of great significance.

[0056] In the sodium-ion battery of the present invention, the positive electrode active material can achieve a positive electrode potential of 4.0V or higher or 4.2V or higher during charging based on the sodium electrode potential reference. In a sodium-ion battery containing such a high-potential positive electrode active material, the capacity retention rate decreases to a large extent, so the configuration of the present invention is of great significance.

[0057] The specific surface area of the positive electrode active material may be 0.1m 2 / g to 1.5m 2 / g, 0.2m 2 / g to 1.2m 2 / g, or 0.3m 2 / g to 1.0m 2 / g. The specific surface area of the positive electrode active material may be 0.1m 2 / g or more, 0.2m 2 / g or more, 0.3m 2 / g or more, 0.4m 2 / g or more, and may be 1.5m 2 / g or less, 1.2m 2 / g or less, 1.0m 2 / g or less, 0.8m 2 / g or less, 0.6m 2 / g or less, 0.5m 2 / g or less, or 0.4m 2 / g or less.

[0058] Regarding the present invention, the magnitude of the specific surface area of the positive electrode active material refers to the magnitude of the contact area with the non-aqueous electrolyte. Therefore, the magnitude of the specific surface area of the positive electrode active material can be used as an indicator of the leaching amount of transition metal ions from the positive electrode active material into the non-aqueous electrolyte.

[0059] The specific surface area of the positive electrode active material can be measured by a gas adsorption method.

[0060] The concentration of dinitrile compounds in non-aqueous electrolytes, expressed in mM, relative to the concentration expressed in m... 2 The ratio of the specific surface area of ​​the positive electrode active material, expressed as / g, can be 200–1500, 400–1000, or 600–700. This ratio can be above 250, 300, 350, 400, 450, 500, 550, 600, or 650, and can be below 1500, 1200, 1000, 900, 850, 800, 750, or 700. This ratio specifies the relationship between the concentration of the dinitrile compound in the non-aqueous electrolyte and the amount of transition metal ions dissolved from the positive electrode active material to the non-aqueous electrolyte. In other words, this ratio indicates the proportion of the dinitrile compound relative to the transition metal ions dissolved from the positive electrode active material in the non-aqueous electrolyte.

[0061] There is no particular limitation on the content of positive electrode active material in the positive electrode active material layer; it can be appropriately set by taking into account factors such as the desired battery capacity.

[0062] There are no particular limitations on the shape and size of the positive electrode active material.

[0063] (Conductive additives and adhesives)

[0064] The positive electrode active material layer can contain conductive additives, binders, etc.

[0065] The conductive additive is not particularly limited and can be, for example, carbon materials, metallic materials, etc. Examples of carbon materials include carbon black such as acetylene black, Ketjen black, furnace black, and thermal black; carbon fibers such as carbon nanotubes and vapor-grown carbon fibers (VGCF); graphite and hard carbon; and coke. Examples of metallic materials include Fe, Cu, Ni, and Al. The conductive additive can be one or more of the above-mentioned materials.

[0066] There is no particular limitation on the content of conductive additives in the positive electrode active material layer; it can be appropriately set considering the desired conductivity, etc.

[0067] <Adhesive>

[0068] Examples of adhesives include fluorinated adhesives such as polyvinylidene fluoride (PVdF) adhesives and polytetrafluoroethylene (PTFE) adhesives; rubber-based adhesives such as styrene-butadiene rubber (SBR) adhesives; olefin-based adhesives such as polypropylene (PP) adhesives and polyethylene (PE) adhesives; cellulose-based adhesives such as carboxymethyl cellulose (CMC) adhesives; and polyacrylic acid (PAA) adhesives. The adhesive may be one or more of the above-mentioned materials.

[0069] There is no particular limitation on the amount of binder in the positive electrode active material layer; it can be appropriately set considering the desired adhesion, etc.

[0070] <Dipple layer>

[0071] As for the membrane constituting the separator layer, there are no particular limitations as long as it has the function of electrically separating the negative electrode active material layer from the positive electrode active material layer. For example, the separator can be a porous sheet made of resins such as polyethylene (PE), polypropylene (PP), polyester, cellulose, and polyamide; porous insulating materials such as non-woven fabric and glass fiber non-woven fabric; or a combination thereof.

[0072] <Negative Electrode Active Material Layer>

[0073] The negative electrode active material layer contains negative electrode active material and may contain conductive additives, binders, etc.

[0074] (Negative electrode active material)

[0075] There are no particular limitations on the negative electrode active material; any material known as a negative electrode active material for sodium-ion batteries can be used. Examples of negative electrode active materials include metallic materials containing sodium, such as sodium metal or sodium alloys; carbon materials such as graphite, hard carbon, and carbon black; sodium-transition metal composite oxides such as sodium titanate; oxides composed of elements other than sodium, such as SiOx; or combinations thereof.

[0076] There is no particular limitation on the content of negative electrode active material in the negative electrode active material layer; it can be appropriately set by taking into account factors such as the desired battery capacity.

[0077] There are no particular restrictions on the shape and size of the negative electrode active material.

[0078] (Conductive additives and adhesives)

[0079] For information on conductive additives and adhesives, please refer to the above description.

[0080] <Negative Electrode Current Collector Layer>

[0081] Examples of materials used as negative electrode current collector layers include SUS, aluminum, copper, nickel, and carbon.

[0082] <Non-aqueous electrolyte>

[0083] In the sodium-ion battery of the present invention, the positive electrode active material layer, the separator layer, and the negative electrode active material layer are impregnated with a non-aqueous electrolyte. The non-aqueous electrolyte comprises an electrolyte salt, a gel-based solvent, and a dinitrile compound.

[0084] (electrolyte salts)

[0085] As an electrolyte salt, there are no particular limitations. For example, it can be inorganic sodium salts such as NaPF6, NaBF4, NaClO4, and NaAsF6; and organic sodium salts such as NaCF3SO3, NaN(CF3SO2)2, NaN(C2F5SO2)2, NaN(FSO2)2, and NaC(CF3SO2)3; or combinations thereof.

[0086] The concentration of electrolyte salts in non-aqueous electrolytes can be 0.5 mol / L to 2.0 mol / L or 0.7 mol / L to 1.5 mol / L.

[0087] (Glyme-based solvent)

[0088] The glycome-based solvent is not particularly limited; for example, it can be a single glycome, a single glycome derivative, a diglycome, a diglycome derivative, a triglycome, a triglycome derivative, or a combination thereof. The glycome-based solvent can be a single glycome, a single glycome derivative, or a combination thereof. If the glycome-based solvent is a single glycome, a single glycome derivative, or a combination thereof, it easily promotes the dissolution of transition metal ions due to its strong stabilizing effect on the coordination of transition metal ions, thus making it significant as a constituent material of the sodium-ion battery of this invention. The glycome-based solvent can be a single glycome.

[0089] In this invention, mono-Glyme refers to 1,2-dimethoxyethane (DME), di-Glyme refers to diethylene glycol dimethyl ether, and tri-Glyme refers to triethylene glycol dimethyl ether.

[0090] In this invention, mono-Glyme derivatives, di-Glyme derivatives, and tri-Glyme derivatives refer to compounds in which at least a portion of the hydrogen atoms of mono-Glyme, di-Glyme, and tri-Glyme are substituted, for example, by hydrocarbons, fluorine, phosphorus, and sulfur. Examples of mono-Glyme derivatives include 1,2-diethoxyethane, 1,2-dimethoxypropane, and 1,2-bis(trifluoromethoxyethane).

[0091] (carbonate-based solvents)

[0092] In the sodium-ion battery of the present invention, the non-aqueous electrolyte may further contain a carbonate-based solvent.

[0093] There are no particular limitations on the carbonate; for example, it can be a cyclic carbonate or a chain carbonate. Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, butene carbonate, and fluoroethylene carbonate. Examples of chain carbonates include dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0094] There is no particular limitation on the mass ratio of carbonate-based solvents to gyme-based solvents; for example, it can be 1:9 to 5:5 or 2:8 to 4:6.

[0095] The non-aqueous electrolyte may further contain other non-aqueous solvents, or it may not contain any. Such non-aqueous solvents may be high-dielectric-constant solvents, low-dielectric-constant solvents, or combinations thereof. Examples of high-dielectric-constant solvents include γ-butyrolactone; sulfolane; N-methyl-2-pyrrolidone (NMP); 1,3-dimethyl-2-imidazolinone (DMI); or combinations thereof. Examples of low-dielectric-constant solvents include acetate esters such as methyl acetate and ethyl acetate; ethers such as 2-methyltetrahydrofuran; or combinations thereof.

[0096] (Dionitrile compounds)

[0097] Dinitrile compounds can inhibit the dissolution of transition metal ions from the positive electrode active material.

[0098] Dinitrile compounds can be compounds with nitrile groups bonded to both ends of a chain-like saturated hydrocarbon compound.

[0099] As a dinitrile compound, there are no particular limitations; for example, it can be a compound with the general formula NC-(CH). n -CN represents a linear compound. In the above formula, n can be 1 to 10, 1 to 6, or 2 to 4. Specifically, examples of such dinitrile compounds include succinate, glutaronitrile, adiponitrile, sebaconitrile, and dodecanedionitrile. The dinitrile compound can be adiponitrile, succinate, or a combination thereof, especially adiponitrile. This effectively improves the battery's capacity retention.

[0100] Dinitrile compounds can be branched compounds. An example of such a dinitrile compound is 2-methylglutaronitrile.

[0101] In non-aqueous electrolytes, the ratio of the concentration of the dinitrile compound to the concentration of the electrolyte salt can be 0.05–0.60, 0.10–0.60, 0.15–0.40, or 0.20–0.30. This ratio can be greater than 0.05, greater than 0.10, greater than 0.15, greater than 0.20, or greater than 0.25, and can be less than 0.60, less than 0.50, less than 0.40, or less than 0.30. This effectively improves the battery's capacity retention.

[0102] In non-aqueous electrolytes, the concentration of the dinitrile compound can be 50 mM–600 mM, 100 mM–600 mM, 150 mM–400 mM, or 200 mM–300 mM. This concentration can be above 50 mM, above 100 mM, above 150 mM, above 200 mM, above 250 mM, or above 275 mM, and can also be below 600 mM, below 500 mM, below 400 mM, below 300 mM, or below 275 mM. This effectively improves the battery's capacity retention.

[0103] (Other ingredients)

[0104] Non-aqueous electrolytes may contain any components other than those mentioned above, or they may not contain any components at all.

[0105] <Shape and thickness of each layer>

[0106] The shape of each of the above layers is not particularly limited; for example, it can be a sheet with a generally planar shape.

[0107] The thickness of each of the above layers is not particularly limited and can be adjusted appropriately according to the structure of the battery.

[0108] <Other Structures>

[0109] The sodium-ion battery of the present invention may include a battery casing that houses the above-mentioned layers and terminals that connect to the current collector layer, etc. These are commonly used in sodium-ion batteries.

[0110] Example

[0111] <<Reference Example 1>>

[0112] <Preparation of Non-Aqueous Electrolytes>

[0113] Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of EC:DMC:EMC = 3:4:3 to obtain a mixed solvent. NaPF6 1 mol / L (1000 mM) was added to this mixed solvent as an electrolyte salt to obtain a non-aqueous electrolyte.

[0114] <Formation of the Positive Electrode Active Material Layer>

[0115] The O3-type layered rock salt oxide, namely NaNi, will be used as the positive electrode active material. 0.33 Fe 0.33 Mn 0.33O2 particles, conductive additives, and binders were mixed / kneaded in a mass ratio of positive electrode active material: conductive additive: binder = 85:10:5 to obtain a positive electrode composite slurry. The obtained positive electrode composite slurry was coated onto an aluminum foil serving as the positive electrode current collector layer using a doctor blade to obtain a coating layer. By drying the coating layer and applying pressure, a positive electrode laminate with a positive electrode active material layer formed on the positive electrode current collector layer was fabricated. The specific surface area of ​​the positive electrode active material, measured by gas adsorption, was 0.4 m². 2 / g.

[0116] <Formation of the Negative Electrode Active Material Layer>

[0117] Hard carbon particles, conductive additives, and binders, serving as the negative electrode active material, are mixed / kneaded in a mass ratio of negative electrode active material: conductive additives: binder = 85:10:5 to obtain a negative electrode composite slurry. The obtained negative electrode composite slurry is then coated onto aluminum foil, serving as the negative electrode current collector layer, using a doctor blade to obtain a coating layer. By drying the coating layer and applying pressure, a negative electrode laminate with a negative electrode active material layer formed on the negative electrode current collector layer is fabricated.

[0118] <Battery Making>

[0119] The positive electrode stack was punched to φ16mm, and the negative electrode stack was punched to φ18mm. A φ20mm polyolefin porous membrane (thickness: 25μm) was placed between the positive and negative electrode stacks to form a membrane layer, thus fabricating the electrode body. The electrode body was housed in a casing, a non-aqueous electrolyte was injected into the casing, and the casing was sealed, thereby fabricating an evaluation sodium-ion secondary battery (CR2032 type button cell).

[0120] <Evaluation of Capacity Maintenance Rate>

[0121] The obtained sodium-ion secondary battery was subjected to three charge-discharge cycles under the following conditions, and the charge-discharge capacity was measured. This charge-discharge capacity was taken as the initial charge-discharge capacity:

[0122] • Charging… Charging method: CCCV, Maximum voltage: 4.2V, C rate: 0.1C, Temperature: 25℃

[0123] • Discharge... Discharge method: CCCV, lower limit voltage: 2.0V, C rate: 0.1C, temperature: 25℃.

[0124] Next, 50 charge-discharge cycles were performed under the following conditions:

[0125] • Charging… Charging method: CC, Maximum voltage: 4.2V, C rate: 1.0C, Temperature: 25℃

[0126] • Discharge... Discharge method: CC, lower limit voltage: 2.0V, C rate: 1.0C, temperature: 25℃.

[0127] Next, one charge-discharge cycle was performed under the following conditions, and the charge-discharge capacity was measured. This charge-discharge capacity was taken as the charge-discharge capacity after 50 cycles:

[0128] • Charging… Charging method: CCCV, Maximum voltage: 4.2V, C rate: 0.1C, Temperature: 25℃

[0129] • Discharge... Discharge method: CCCV, Lower limit voltage: 2.0V, C rate: 0.1C, Temperature: 25℃

[0130] Next, 50 charge-discharge cycles were performed under the following conditions.

[0131] • Charging… Charging method: CC, Maximum voltage: 4.2V, C rate: 1.0C, Temperature: 25℃

[0132] • Discharge... Discharge method: CC, lower limit voltage: 2.0V, C rate: 1.0C, temperature: 25℃.

[0133] Next, one charge-discharge cycle was performed under the following conditions, and the charge-discharge capacity was measured. This charge-discharge capacity was taken as the charge-discharge capacity after 100 cycles:

[0134] • Charging… Charging method: CCCV, Maximum voltage: 4.2V, C rate: 0.1C, Temperature: 25℃

[0135] • Discharge... Discharge method: CCCV, lower limit voltage: 2.0V, C rate: 0.1C, temperature: 25℃.

[0136] The ratio of charge / discharge capacity after 50 cycles to the initial charge / discharge capacity and the ratio of charge / discharge capacity after 100 cycles to the initial charge / discharge capacity were calculated and used as the capacity retention rate. The capacity retention rate after 100 cycles is shown in Table 1.

[0137] <<Reference Example 2>>

[0138] In the preparation of the non-aqueous electrolyte, except that 570 mM adiponitrile (AdN) as a dinitrile compound was further added to the mixed solvent, the non-aqueous electrolyte and battery of Reference Example 2 were obtained in the same manner as in Reference Example 1, and were evaluated. The results are shown in Table 1.

[0139] [Table 1]

[0140]

[0141] As shown in Table 1, in the reference example battery where the non-aqueous electrolyte solvent was a mixture of EC, DMC, and EMC, no effect of AdN addition was observed. This was also observed in the results related to capacity retention after 50 cycles. This is believed to be because, in the reference example battery, the non-aqueous electrolyte did not contain a glycole-based solvent, and therefore excessive dissolution of transition metal ions from the positive electrode active material did not occur, preventing AdN from functioning as previously speculated.

[0142] <<Examples 1-5>>

[0143] In the preparation of the non-aqueous electrolyte, except that EC (as a carbonate solvent) and dimethoxyethane (DME) (as a gypsum solvent) were mixed in a mass ratio of EC:DME=3:7 to obtain a mixed solvent, and the AdN concentration was set as described in Table 1 below, the non-aqueous electrolyte and battery were obtained in the same manner as in Reference Example 2, and the capacity retention rate was calculated. The capacity retention rate after 100 cycles is shown in Table 2.

[0144] <<Comparative Example 1>>

[0145] In the preparation of the non-aqueous electrolyte, except that AdN was not added to the mixed solvent, the non-aqueous electrolyte and battery were obtained in the same manner as in Examples 1-5, and the capacity retention rate was calculated. The capacity retention rate after 100 cycles is shown in Table 2.

[0146] <Evaluation of the solubility of transition metal ions based on ICP luminescence analysis>

[0147] The batteries of Example 3 and Comparative Example 1 were disassembled, and the positive electrode active material layer was removed. The material was then cleaned with a cleaning solution composed of the non-aqueous electrolyte solvent components (containing AdN) of each example. The solution in which the cleaned positive electrode active material layer was dissolved in mixed acid was used as the test sample for ICP-luminescence analysis. The low amount of transition metal detected by this analysis indicates a low leaching of transition metal ions into the non-aqueous electrolyte solvent. The results are shown in Table 2.

[0148] [Table 2]

[0149]

[0150] As shown in Table 2, in the examples where the non-aqueous electrolyte solvent is a mixed solvent of EC and DME and the non-aqueous electrolyte contains AdN, the capacity retention after 100 cycles is high. The same is true for the results relating to capacity retention after 50 cycles.

[0151] Furthermore, in the battery of Example 3, where the non-aqueous electrolyte contained AdN, the amount of transition metal ions dissolved was less compared to that of Comparative Example 1, where the non-aqueous electrolyte did not contain AdN. This supports the above-mentioned hypothetical mechanism: the dinitrile compound hinders the coordination of transition metal ions by the Glyme-based solvent, thereby suppressing the dissolution of transition metal ions into the non-aqueous electrolyte.

[0152] Symbol Explanation

[0153] 1-Sodium-ion battery, 10-Positive electrode current collector layer, 20-Positive electrode active material layer, 30-Separator layer, 40-Negative electrode active material layer, 50-Negative electrode current collector layer.

Claims

1. A sodium-ion battery, characterized in that, It sequentially comprises a positive electrode active material layer, a separator layer, and a negative electrode active material layer. The positive electrode active material layer, the separator layer, and the negative electrode active material layer are impregnated with a non-aqueous electrolyte. The positive electrode active material layer contains a positive electrode active material comprising transition metal elements. The non-aqueous electrolyte contains electrolyte salts, Glyme-based solvents, and dinitrile compounds.

2. The sodium-ion battery according to claim 1, characterized in that, The non-aqueous electrolyte also contains carbonate-based solvents.

3. The sodium-ion battery according to claim 1 or 2, characterized in that, The positive electrode active material is a layered rock salt type oxide. The gyme-based solvent is a single gyme, a single gyme derivative, or a combination thereof, and The dinitrile compound is adiponitrile, succinate, or a combination thereof.

4. The sodium-ion battery according to claim 3, characterized in that, The concentration of the dinitrile compound in the non-aqueous electrolyte, expressed in mM, relative to the concentration expressed in m... 2 The ratio of the specific surface area of ​​the positive electrode active material, expressed as / g, is 200 to 1500.

5. The sodium-ion battery according to claim 4, characterized in that, In the non-aqueous electrolyte, the concentration of the dinitrile compound relative to the concentration of the electrolyte salt is 0.05 to 0.

60.

6. The sodium-ion battery according to claim 5, characterized in that, In the non-aqueous electrolyte, the concentration of the dinitrile compound is 50 mM to 600 mM.

Citation Information

Patent Citations

  • Electrolyte for sodium ion battery

    JP2010165674A

  • Sodium ion secondary battery

    JP2016085890A

  • Positive electrode active material for sodium secondary battery

    JP2023003666A

  • Electrolyte for Na-ion batteries

    JP2023545564A